Design Of Gravity Conveyor At PT Rukun Mitra Sejati Malang Taking Into Account The Value Of Ergonomics And Worker Productivity - W T Bhirawa; Basuki Arianto; Adnanto Hendri Prasetyo; Tri Susilo; Indramwan Indramwan; Darmawan Darmawan; Dimpo Sinaga (Universitas Ibn Khaldun Bogor, 2023)
Fast Moving Consumer Goods are the focus of the distribution company PT Rukun Mitra Sejati. The procedure of loading and unloading cargo is one of them. When using incorrect work processes, employees that carry out the process frequently complain about fatigue, back ache, neck pain, and arm pain.In the study, postures were examined in order to determine the root causes of complaints related to musculoskeletal disorders (MSDs), using the REBA, RULA, and Nordic Body Map (NBM) questionnaire methodologies. The examination of the work position posture using the REBA method produced a recapitulation score of 11, which indicates that it has a very high risk and needs to be replaced right away in the job application. According to the results of the Nordic Body Map (NBM) questionnaire, 41% of the respondents' limbs do not experience any discomfort, whereas 59% of the respondents' limbs experience pain and are at risk of harm. Gravity Conveyors are tools used to move goods from trucks to warehouses that can be adjusted to the height required when the loading and unloading process is carried out, with a height size near the truck of 0.99m (99.5cm), the height on the warehouse floor is 0.56m (55.93cm), and the width is 0.44m (43cm) adjusted for people who move goods from the conveyor to the pallet does not bend. The anthropometric technique is used in the design of the gravity conveyor to provide users a sense of comfort.